Optimization of the Learning Process of Handball Exercises - Ibragimov Alisher Karomatovich; Ravshanov Amirali Alimardon o’g’li (International Journal on Orange Technologies, 2022)
The article raises the problem of optimization of the educational process in physical education classes at the handball department. Among the students of 1-2 courses aged 17-20 years old, who go in for handball, priority motives were identified that played a major role in the choice of this sport out of fifteen others presented at the Faculty of Physical Education of BSU. " In the article, we present the main forms of physical education used in the lessons of the educational department of handball. A comparative analysis of training programs of various orientations during the learning process has been carried out. The main factors of optimization of health-improving physical education classes for students involved in the handball department have been determined.